Implementación de la Metodología Lean Construction LPS plan maestro LPDS ejecución integrada de proyectos en la gestión de proyectos para la construcción de obras municipales como la regeneración urbana en la ciudad de Guayaquil - Consuegra Silva, Joel Andrés (2024)
The construction sector is the largest source of employment and investment that a country can have, therefore, project management, growth and productivity are necessary issues that must be improved and renewed. Its development gives way to new technologies and also to new theoretical bases, where it is intended to see production in construction as a process of transformation of flows, creating systems that allow optimizing, reducing or eliminating flows to improve project delivery times...........